Highly adhesive conductive paste and method for preparing the same

CN122968035APending Publication Date: 2026-10-23NANNING YUQIANG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611029446.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种高粘结性导电浆料及其制备方法,解决了现阶段高粘结性导电浆料柔韧性差,且多次循环后电池性能出现明显下降的问题

Benefits of technology

[0013]改性聚偏氟乙烯通过化学键引入了柔性聚氟硅氧烷侧链,降低了聚合物的结晶度,提升了柔韧性,在导电浆料用于极片时,能够吸收极片循环中的体积变化应力,大幅减少涂层的开裂和掉粉,改性添加剂作为刚性节点,提供了力学支撑和额外的短程导电通路,让网络更牢固,改性添加剂以纳米二氧化硅为内核在表面碳层中插入了聚硅氧烷中间层则部分转化的硅氧碳或碳化硅陶瓷相,使得在多次循环碳包覆不会出现脱落,同时含有硫和氮的掺杂,进而提高了碳包覆层的本征电子导电率。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of high cohesive conductive paste and preparation method thereof, the conductive paste includes the following weight parts raw materials: modified polyvinylidene fluoride 12-18 parts, modified additive 8-10 parts, carbon nanotube 3-5 parts and N-methyl pyrrolidone 70-80 parts, modified polyvinylidene fluoride is introduced by chemical bond with flexible polyfluorosilicone side chain, reduce the crystallinity of polymer, improve flexibility, when conductive paste is used for pole piece, it can absorb the volume change stress in pole piece cycle, significantly reduce the cracking and powder of coating, modified additive as rigid node, provide mechanical support and additional short-range conductive path, modified additive is inserted into polysiloxane intermediate layer in surface carbon layer with nanometer silicon dioxide as core, then partially converted silicon oxycarbide or silicon carbide ceramic phase, so that carbon coating does not appear to fall off in multiple cycles, and the doping of containing sulfur and nitrogen, and then improve the intrinsic electronic conductivity of carbon coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive paste preparation technology, specifically to a highly adhesive conductive paste and its preparation method. Background Technology

[0002] With the increasing demands for energy density, fast-charging performance, and cycle life of lithium-ion batteries from new energy vehicles and large-scale energy storage systems, the stability of electrode structure has become a key bottleneck restricting battery performance. During electrode preparation, the conductive paste plays a crucial role in constructing electron transport pathways, providing mechanical integrity, and ensuring interfacial adhesion. Its performance directly determines the rate performance, cycle life, and safety characteristics of the electrode. Homopolymer PVDF has high crystallinity and rigid molecular chains, resulting in brittleness after film formation. During battery charging and discharging, especially when using high-capacity silicon-based anodes or high-density thick electrodes, the active material undergoes significant volume expansion and contraction. The rigid PVDF binder cannot effectively dissipate stress, leading to microcracks in the coating. These microcracks accumulate with each cycle, causing the conductive network to break and the active material to peel off from the current collector, ultimately resulting in a continuous increase in battery internal resistance and accelerated capacity decay. Summary of the Invention

[0003] The purpose of this invention is to provide a highly adhesive conductive slurry and its preparation method, which solves the problems of poor flexibility of current highly adhesive conductive slurries and significant decline in battery performance after multiple cycles.

[0004] The objective of this invention can be achieved through the following technical solutions: A highly adhesive conductive paste and its preparation method, specifically including the following steps: Step A1: Dissolve lithium dimethylvinylsilane in tetrahydrofuran, purge with nitrogen, stir and add trifluoropropylmethylcyclotrisiloxane at 150-200 r / min and 0℃, heat to 25-30℃ and react for 18-20 h, then add trimethylchlorosilane and continue the reaction for 1-1.5 h to obtain monoalkenyl polysiloxane; Step A2: Dissolve polyvinylidene fluoride in N,N-dimethylformamide, purge with nitrogen, and stir at a speed of 150-200 r / min and a temperature of 70-75℃. Add benzoyl peroxide and monoalkenyl polysiloxane, and react for 8-10 h. Add anhydrous ethanol, filter to remove the filtrate, and dry the substrate to obtain modified polyvinylidene fluoride. Step A3: Weigh the following raw materials in parts by weight: 12-18 parts of modified polyvinylidene fluoride, 8-10 parts of modified additives, 3-5 parts of carbon nanotubes and 70-80 parts of N-methylpyrrolidone. Mix the raw materials evenly to obtain a highly adhesive conductive paste.

[0005] Furthermore, the molar ratio of lithium dimethylvinylsilanolate, trifluoropropylmethylcyclotrisiloxane, and trimethylchlorosilane in step A1 is 1:4:1.

[0006] Furthermore, the mass ratio of polyvinylidene fluoride, benzoyl peroxide, and monoalkenyl polysiloxane in step A2 is 2:0.005:0.1.

[0007] Furthermore, the modified additive is prepared by the following steps: Step B1: Dissolve lithium trimethylsilyl alcohol in tetrahydrofuran, purge with nitrogen, and stir at 150-200 r / min and 0°C. Add octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane, heat to 25-30°C, and react for 18-20 h. Then add dimethylchlorosilane and continue the reaction for 1-1.5 h to obtain polyene polysiloxane. Mix polyene polysiloxane, mercaptoethanol, benzoin dimethyl ether, and toluene, purge with nitrogen, and react at 200-300 r / min, 20-25°C, and 365 nm ultraviolet light for 2-3 h to obtain pretreated polysiloxane. Step B2: Mix pretreated polysiloxane, allyl alcohol glycidyl ether, caster catalyst and toluene, purge with nitrogen, and react for 6-8 hours at a speed of 150-200 r / min and a temperature of 80-85℃ to obtain modified polysiloxane. Disperse nano-silica in ethanol, stir and add γ-aminopropyltriethoxysilane and deionized water at a speed of 200-300 r / min and a temperature of 60-65℃, and react for 3-5 hours to obtain aminated silica. Step B3: Mix aminated silica, modified polysiloxane, and xylene. Stir and add triethylamine at 300-500 r / min and 80-90℃ for 8-10 h to obtain modified silica. Disperse the modified silica in deionized water. Stir and add glucose at 600-800 r / min and 20-25℃ for 30-40 min. Place the mixture in a hydrothermal reactor and react at 180-185℃ for 10-12 h to obtain a precursor. Place the precursor in a tube furnace and purge with nitrogen. Heat to 800-900℃ at a rate of 5℃ / min and hold for 2-3 h to obtain the modified additive.

[0008] Furthermore, in step B1, the molar ratio of trimethylsilyllithium, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, and dimethylchlorosilane is 1:5:0.5:1, the molar ratio of the double bond on the polyene polysiloxane to mercaptoethanol is 1:1, and the amount of benzoin dimethyl ether is 1% of the mass of mercaptoethanol.

[0009] Furthermore, in step B2, the molar ratio of the pretreated polysiloxane and allyl alcohol glycidyl ether is 1:1, the amount of caster catalyst is 0.1% of the mass of allyl alcohol glycidyl ether, and the amount of γ-aminopropyltriethoxysilane is 3% of the mass of nano silica.

[0010] Furthermore, in step B3, the molar ratio of the amino group on the aminated silica to the modified polysiloxane is 1:1, the amount of triethylamine is 2% of the mass of the modified polysiloxane, and the ratio of modified silica, deionized water and glucose is 1g:100mL:5g.

[0011] The beneficial effects of this invention are as follows: This application discloses a highly adhesive conductive paste comprising the following raw materials: 12-18 parts of modified polyvinylidene fluoride, 8-10 parts of modifying additives, 3-5 parts of carbon nanotubes, and 70-80 parts of N-methylpyrrolidone. The modified polyvinylidene fluoride is polymerized using dimethylvinylsilane lithium as an initiator and trifluoropropylmethylcyclotrisiloxane as a monomer to form a polysiloxane with a vinyl end and a silane lithium end. Trimethylchlorosilane is then added, causing the Si-Cl bond on the trimethylchlorosilane to react with the silane lithium to obtain a monoalkenyl polysiloxane. The polyvinylidene fluoride is then treated with benzoyl peroxide to graft the monoalkenyl polysiloxane onto the polyvinylidene fluoride, thus obtaining the modified polyvinylidene fluoride.

[0012] The modified additive uses trimethylsilyllithium as an initiator and octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane as polymerization monomers to form a polysiloxane with lithium silanolate at one end and double bonds in the side chain. Dimethylchlorosilane is then added, causing the Si-Cl bonds on the dimethylchlorosilane to react with the lithium silanolate, producing a polyene-based polysiloxane. The polyene-based polysiloxane is then reacted with mercaptoethanol, causing the double bonds on the polyene-based polysiloxane to react with the mercapto groups on the mercaptoethanol, producing a pretreated polysiloxane. Finally, the pretreated polysiloxane is reacted with allyl glycidyl ether, causing the Si-H bonds on the pretreated polysiloxane to react with the allyl groups in the side chain. Modified polysiloxane is prepared by reacting the double bonds on propanol glycidyl ether. Nano-silica is treated with γ-aminopropyltriethoxysilane to graft amino groups onto the surface, thus preparing aminated silica. Aminated silica is then reacted with modified polysiloxane to react the amino groups on the aminated silica with the epoxy groups on the modified polysiloxane, thus preparing modified silica. Modified silica is then treated with glucose to adsorb the hydroxyl and aldehyde groups on the glucose onto the surface of the modified silica via hydrogen bonds, thus preparing a precursor. The precursor is then calcined under a nitrogen atmosphere to form a carbon layer, thus preparing a modified additive.

[0013] Modified polyvinylidene fluoride (PVDF) introduces flexible polyfluorosiloxane side chains through chemical bonds, reducing the crystallinity of the polymer and improving its flexibility. When used in conductive pastes for electrodes, it can absorb the volume change stress during electrode cycling, significantly reducing coating cracking and powder shedding. The modified additives, acting as rigid nodes, provide mechanical support and additional short-range conductive pathways, making the network more robust. The modified additives, with nano-silica as the core, insert polysiloxane intermediate layers into the surface carbon layer, which are partially converted into silicon-oxygen-carbon or silicon carbide ceramic phases, preventing the carbon coating from falling off after multiple cycles. They also contain sulfur and nitrogen dopants, thereby improving the intrinsic electronic conductivity of the carbon coating layer. Detailed Implementation

[0014] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] Example 1: A method for preparing a highly adhesive conductive paste, specifically including the following steps: Step A1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran and protected by nitrogen. Under the conditions of 150 r / min and 0℃, trifluoropropylmethylcyclotrisiloxane was added while stirring. The temperature was raised to 25℃ and the reaction was carried out for 18 h. Then, trimethylchlorosilane was added and the reaction was continued for 1 h to obtain monoalkenyl polysiloxane. Step A2: Dissolve polyvinylidene fluoride in N,N-dimethylformamide, purge with nitrogen, stir at 150 r / min and 70 °C, add benzoyl peroxide and monoalkenyl polysiloxane, react for 8 h, add anhydrous ethanol, filter to remove filtrate, dry the substrate to obtain modified polyvinylidene fluoride. Step A3: Weigh the following raw materials in parts by weight: 12 parts modified polyvinylidene fluoride, 8 parts modified additives, 3 parts carbon nanotubes and 70 parts N-methylpyrrolidone. Mix the raw materials evenly to obtain a highly adhesive conductive paste.

[0016] The molar ratio of lithium dimethylvinylsilane, trifluoropropylmethylcyclotrisiloxane and trimethylchlorosilane in step A1 is 1:4:1.

[0017] The mass ratio of polyvinylidene fluoride, benzoyl peroxide, and monoalkenyl polysiloxane in step A2 is 2:0.005:0.1.

[0018] The modified additive is prepared by the following steps: Step B1: Lithium trimethylsilyl alcohol was dissolved in tetrahydrofuran under nitrogen protection. Under the conditions of 150 r / min and 0°C, octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added while stirring. The temperature was raised to 25°C and the reaction was carried out for 18 h. Then, dimethylchlorosilane was added and the reaction was continued for 1 h to obtain polyene polysiloxane. Polyene polysiloxane, mercaptoethanol, benzoin dimethyl ether and toluene were mixed and under nitrogen protection. Under the conditions of 200 r / min, 20°C and 365 nm ultraviolet light irradiation, the reaction was carried out for 2 h to obtain pretreated polysiloxane. Step B2: Pretreated polysiloxane, allyl alcohol glycidyl ether, caster catalyst and toluene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 6 hours at a speed of 150 r / min and a temperature of 80 °C to obtain modified polysiloxane. Nano-silica is dispersed in ethanol, and γ-aminopropyltriethoxysilane and deionized water are added at a speed of 200 r / min and a temperature of 60 °C. The mixture is then reacted for 3 hours to obtain aminated silica. Step B3: Aminated silica, modified polysiloxane, and xylene are mixed and stirred at 300 r / min and 80°C, while triethylamine is added. The mixture is reacted for 8 hours to obtain modified silica. The modified silica is dispersed in deionized water and stirred at 600 r / min and 20°C, while glucose is added. After stirring for 30 minutes, the mixture is placed in a hydrothermal reactor and reacted at 180°C for 10 hours to obtain a precursor. The precursor is placed in a tube furnace and protected with nitrogen. The temperature is raised to 800°C at a rate of 5°C / min and held for 2 hours to obtain the modified additive.

[0019] The molar ratio of trimethylsilyllithium, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and dimethylchlorosilane in step B1 is 1:5:0.5:1, the molar ratio of the double bond on the polyene polysiloxane to mercaptoethanol is 1:1, and the amount of benzoin dimethyl ether is 1% of the mass of mercaptoethanol.

[0020] In step B2, the molar ratio of the pretreated polysiloxane and allyl alcohol glycidyl ether is 1:1, the amount of caster catalyst is 0.1% of the mass of allyl alcohol glycidyl ether, and the amount of γ-aminopropyltriethoxysilane is 3% of the mass of nano silica.

[0021] In step B3, the molar ratio of the amino group on the aminated silica to the modified polysiloxane is 1:1, the amount of triethylamine is 2% of the mass of the modified polysiloxane, and the ratio of modified silica, deionized water and glucose is 1g:100mL:5g.

[0022] Example 2, a method for preparing a highly adhesive conductive paste, specifically includes the following steps: Step A1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran and protected with nitrogen. Under the conditions of 150 r / min and 0℃, trifluoropropylmethylcyclotrisiloxane was added while stirring. The temperature was raised to 30℃ and the reaction was carried out for 18 h. Then, trimethylchlorosilane was added and the reaction was continued for 1.5 h to obtain monoalkenyl polysiloxane. Step A2: Dissolve polyvinylidene fluoride in N,N-dimethylformamide, purge with nitrogen, stir at 150 r / min and 75 °C, add benzoyl peroxide and monoalkenyl polysiloxane, react for 9 h, add anhydrous ethanol, filter to remove filtrate, dry the substrate to obtain modified polyvinylidene fluoride. Step A3: Weigh the following raw materials in parts by weight: 15 parts modified polyvinylidene fluoride, 9 parts modified additives, 4 parts carbon nanotubes and 75 parts N-methylpyrrolidone. Mix the raw materials evenly to obtain a highly adhesive conductive paste.

[0023] The molar ratio of lithium dimethylvinylsilane, trifluoropropylmethylcyclotrisiloxane and trimethylchlorosilane in step A1 is 1:4:1.

[0024] The mass ratio of polyvinylidene fluoride, benzoyl peroxide, and monoalkenyl polysiloxane in step A2 is 2:0.005:0.1.

[0025] The modified additive is prepared by the following steps: Step B1: Lithium trimethylsilyl alcohol was dissolved in tetrahydrofuran under nitrogen protection. The mixture was stirred at 200 r / min and 0°C, and octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added. The temperature was raised to 25°C and the reaction was carried out for 19 hours. Then, dimethylchlorosilane was added, and the reaction was continued for 1.3 hours to obtain polyene polysiloxane. Polyene polysiloxane, mercaptoethanol, benzoin dimethyl ether, and toluene were mixed and reacted under nitrogen protection at 200 r / min, 25°C, and 365 nm ultraviolet light irradiation for 2 hours to obtain pretreated polysiloxane. Step B2: Pretreated polysiloxane, allyl alcohol glycidyl ether, caster catalyst and toluene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 7 hours at a speed of 200 r / min and a temperature of 80 °C to obtain modified polysiloxane. Nano-silica is dispersed in ethanol, and γ-aminopropyltriethoxysilane and deionized water are added under stirring at a speed of 200 r / min and a temperature of 65 °C. The mixture is reacted for 4 hours to obtain aminated silica. Step B3: Aminated silica, modified polysiloxane, and xylene are mixed and stirred at 300 r / min and 85°C, while triethylamine is added. The mixture is reacted for 9 hours to obtain modified silica. The modified silica is dispersed in deionized water and stirred at 600 r / min and 25°C, while glucose is added. After stirring for 35 minutes, the mixture is placed in a hydrothermal reactor and reacted at 185°C for 10 hours to obtain a precursor. The precursor is placed in a tube furnace and protected with nitrogen. The temperature is raised to 850°C at a rate of 5°C / min and held for 3 hours to obtain the modified additive.

[0026] The molar ratio of trimethylsilyllithium, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and dimethylchlorosilane in step B1 is 1:5:0.5:1, the molar ratio of the double bond on the polyene polysiloxane to mercaptoethanol is 1:1, and the amount of benzoin dimethyl ether is 1% of the mass of mercaptoethanol.

[0027] In step B2, the molar ratio of the pretreated polysiloxane and allyl alcohol glycidyl ether is 1:1, the amount of caster catalyst is 0.1% of the mass of allyl alcohol glycidyl ether, and the amount of γ-aminopropyltriethoxysilane is 3% of the mass of nano silica.

[0028] In step B3, the molar ratio of the amino group on the aminated silica to the modified polysiloxane is 1:1, the amount of triethylamine is 2% of the mass of the modified polysiloxane, and the ratio of modified silica, deionized water and glucose is 1g:100mL:5g.

[0029] Example 3, a method for preparing a highly adhesive conductive paste, specifically includes the following steps: Step A1: Lithium dimethylvinylsilane was dissolved in tetrahydrofuran and protected with nitrogen. Under the conditions of 200 r / min and 0℃, trifluoropropylmethylcyclotrisiloxane was added while stirring. The temperature was raised to 30℃ and the reaction was carried out for 20 h. Then, trimethylchlorosilane was added and the reaction was continued for 1.5 h to obtain monoalkenyl polysiloxane. Step A2: Dissolve polyvinylidene fluoride in N,N-dimethylformamide, purge with nitrogen, stir at 200 r / min and 75 °C, add benzoyl peroxide and monoalkenyl polysiloxane, react for 10 h, add anhydrous ethanol, filter to remove filtrate, dry the substrate to obtain modified polyvinylidene fluoride; Step A3: Weigh the following raw materials in parts by weight: 18 parts modified polyvinylidene fluoride, 10 parts modified additives, 5 parts carbon nanotubes and 80 parts N-methylpyrrolidone. Mix the raw materials evenly to obtain a highly adhesive conductive paste.

[0030] The molar ratio of lithium dimethylvinylsilane, trifluoropropylmethylcyclotrisiloxane and trimethylchlorosilane in step A1 is 1:4:1.

[0031] The mass ratio of polyvinylidene fluoride, benzoyl peroxide, and monoalkenyl polysiloxane in step A2 is 2:0.005:0.1.

[0032] The modified additive is prepared by the following steps: Step B1: Lithium trimethylsilyl alcohol was dissolved in tetrahydrofuran under nitrogen protection. The mixture was stirred at 200 r / min and 0°C, and octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added. The mixture was heated to 30°C and reacted for 20 h. Then, dimethylchlorosilane was added, and the reaction continued for 1.5 h to obtain polyene polysiloxane. Polyene polysiloxane, mercaptoethanol, benzoin dimethyl ether, and toluene were mixed and reacted under nitrogen protection at 300 r / min, 25°C, and 365 nm ultraviolet light irradiation for 3 h to obtain pretreated polysiloxane. Step B2: Pretreated polysiloxane, allyl alcohol glycidyl ether, caster catalyst and toluene are mixed, and nitrogen gas is introduced for protection. The mixture is reacted for 8 hours at a speed of 200 r / min and a temperature of 85℃ to obtain modified polysiloxane. Nano-silica is dispersed in ethanol, and γ-aminopropyltriethoxysilane and deionized water are added under stirring at a speed of 300 r / min and a temperature of 65℃. The mixture is reacted for 5 hours to obtain aminated silica. Step B3: Aminated silica, modified polysiloxane, and xylene are mixed and stirred at 500 r / min and 90°C, while triethylamine is added. The mixture is reacted for 10 h to obtain modified silica. The modified silica is dispersed in deionized water and stirred at 800 r / min and 25°C, while glucose is added. After stirring for 40 min, the mixture is placed in a hydrothermal reactor and reacted at 185°C for 12 h to obtain a precursor. The precursor is placed in a tube furnace and protected with nitrogen. The temperature is raised to 900°C at a rate of 5°C / min and held for 3 h to obtain the modified additive.

[0033] The molar ratio of trimethylsilyllithium, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and dimethylchlorosilane in step B1 is 1:5:0.5:1, the molar ratio of the double bond on the polyene polysiloxane to mercaptoethanol is 1:1, and the amount of benzoin dimethyl ether is 1% of the mass of mercaptoethanol.

[0034] In step B2, the molar ratio of the pretreated polysiloxane and allyl alcohol glycidyl ether is 1:1, the amount of caster catalyst is 0.1% of the mass of allyl alcohol glycidyl ether, and the amount of γ-aminopropyltriethoxysilane is 3% of the mass of nano silica.

[0035] In step B3, the molar ratio of the amino group on the aminated silica to the modified polysiloxane is 1:1, the amount of triethylamine is 2% of the mass of the modified polysiloxane, and the ratio of modified silica, deionized water and glucose is 1g:100mL:5g.

[0036] Comparative Example 1: This comparative example uses polyvinylidene fluoride instead of modified polyvinylidene fluoride, while the other steps are the same as in Example 1.

[0037] Comparative Example 2: This comparative example uses aminated silica instead of modified silica, but the other steps are the same as in Example 1.

[0038] Comparative Example 3: This comparative example uses carbon black instead of the modifying additives, but the other steps are the same as in Example 1.

[0039] The conductive pastes prepared in Examples 1-3 and Comparative Examples 1-3 were sprayed onto aluminum foil to form samples. The samples were then pressed tightly against a 5mm diameter shaft and bent uniformly 180° within 3 seconds. The coating at the bend was observed with a magnifying glass to check for cracks or peeling. The samples were then hot-pressed and cut into 13mm diameter pieces. A Celgard 2400 separator, gaskets, spring contacts, and a CR2032 button cell battery casing were used. The electrolyte was LiPF6 (ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a 1:1:1 volume ratio) to prepare battery samples. The rate performance and cycle performance of the battery were tested using the Blue Electric CT2100A testing system. The test voltage was 2.5-4.2V, with 1C / 1C constant current charge and discharge, and 1000 cycles. The capacity retention rate was measured. The charging rate was fixed at 0.5C, and the discharge rates were 0.2C, 0.5C, 1C, 2C, 3C and 5C, with 5 cycles for each, followed by 5 cycles at 0.2C. The positive electrode was 2.5-4.2V and the negative electrode was 0.01-1.5V. The capacity retention rate and recovery rate at each rate were calculated based on the 0.2C reversible capacity. The test results are shown in Table 1 below.

[0040] Table 1 Coating appearance Microcracks, no peeling Microcracks, no peeling Microcracks, no peeling Cracks appeared Microcracks, no peeling Microcracks, no peeling Capacity retention rate % 94.5 93.2 91.0 78.1 82.4 84.5 5C rate capacity retention % 76.1 74.5 72.3 60.6 66.3 64.2 Recovery rate % 99.2 98.8 98.5 88.3 92.7 93.5 As shown in Table 1, this application has excellent flexibility, interface stability, and long-lasting conductive network.

[0041] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a highly adhesive conductive paste, characterized in that: Specifically, the steps include the following: Step A1: Dissolve lithium dimethylvinylsilane in tetrahydrofuran, purge with nitrogen for protection, stir and add trifluoropropylmethylcyclotrisiloxane, heat and react, then add trimethylchlorosilane and continue the reaction to obtain monoalkenyl polysiloxane. Step A2: Dissolve polyvinylidene fluoride in N,N-dimethylformamide, purge with nitrogen for protection, stir and add benzoyl peroxide and monoalkenyl polysiloxane, react, add anhydrous ethanol, filter to remove filtrate, dry the substrate to obtain modified polyvinylidene fluoride. Step A3: Weigh the following raw materials in parts by weight: 12-18 parts of modified polyvinylidene fluoride, 8-10 parts of modified additives, 3-5 parts of carbon nanotubes and 70-80 parts of N-methylpyrrolidone. Mix the raw materials evenly to obtain a highly adhesive conductive paste.

2. The highly adhesive conductive paste and its preparation method according to claim 1, characterized in that: The molar ratio of lithium dimethylvinylsilane, trifluoropropylmethylcyclotrisiloxane and trimethylchlorosilane in step A1 is 1:4:

1.

3. The highly adhesive conductive paste and its preparation method according to claim 1, characterized in that: The mass ratio of polyvinylidene fluoride, benzoyl peroxide, and monoalkenyl polysiloxane in step A2 is 2:0.005:0.

1.

4. The highly adhesive conductive paste and its preparation method according to claim 1, characterized in that: The modified additive is prepared by the following steps: Step B1: Dissolve lithium trimethylsilyl alcohol in tetrahydrofuran, purge with nitrogen, stir and add octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane, heat and react, then add dimethylchlorosilane and continue the reaction to prepare polyene polysiloxane. Mix polyene polysiloxane, mercaptoethanol, benzoin dimethyl ether and toluene, purge with nitrogen, and react under ultraviolet light to obtain pretreated polysiloxane. Step B2: Mix pretreated polysiloxane, allyl alcohol glycidyl ether, caster catalyst and toluene, purge with nitrogen and react to obtain modified polysiloxane. Disperse nano-silica in ethanol, stir and add γ-aminopropyltriethoxysilane and deionized water and react to obtain aminated silica. Step B3: Mix aminated silica, modified polysiloxane and xylene, stir and add triethylamine to react and obtain modified silica. Disperse the modified silica in deionized water, stir and add glucose. After stirring, place it in a hydrothermal reactor to react and obtain a precursor. Place the precursor in a tube furnace, purge with nitrogen for protection, heat and hold to obtain the modified additive.

5. The highly adhesive conductive paste and its preparation method according to claim 4, characterized in that: The molar ratio of trimethylsilyllithium, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane and dimethylchlorosilane in step B1 is 1:5:0.5:1, and the molar ratio of the double bond on the polyene polysiloxane and mercaptoethanol is 1:

1.

6. The highly adhesive conductive paste and its preparation method according to claim 4, characterized in that: The molar ratio of the pretreated polysiloxane and allyl alcohol glycidyl ether in step B2 is 1:1, and the amount of γ-aminopropyltriethoxysilane used is 3% of the mass of nano silica.

7. The highly adhesive conductive paste and its preparation method according to claim 4, characterized in that: The molar ratio of the amino group on the aminated silica and the modified polysiloxane in step B3 is 1:1, and the ratio of modified silica, deionized water and glucose is 1g:100mL:5g.

8. A highly adhesive conductive paste, characterized in that: It is prepared by any one of the preparation methods described in claims 1-7.